Regional Brain Atrophy in Mouse Models of Neuronal Ceroid Lipofuscinosis: A New Rostrocaudal Perspective. (September 2013) - Kühl, Thomas G.; Dihanich, Sybille; Wong, Andrew M. S.; Cooper, Jonathan D.
The neuronal ceroid lipofuscinoses (Batten disease) are collectively the most common inherited neurodegenerative disorder of childhood. Mouse models of neuronal ceroid lipofuscinosis represent a powerful resource for investigating the underlying disease mechanisms, which remain poorly understood. Here we present a new rostrocaudal analysis of regional brain volume rather than focusing on central nervous system structures that can be affected. This has revealed an earlier onset of regional atrophy than was suspected in infantile neuronal ceroid lipofuscinosis (or CLN1 disease, infantile), with a greater involvement of rostral structures. We have also provided the first description of regional atrophy in severely affected mice with the juvenile variant (CLN3 disease, juvenile). These data reveal new perspectives on how the central nervous system is affected in these disorders, which have implications for judging the efficacy of therapeutic strategies in preclinical studies.